Optimization of the electrical signal generation of a microbial fuel cell for sensor applications - Duan Dong Ta; Linh Dam Thi Mai; Hai The Pham (Vietnam Journal of Science, Technology and Engineering, 2020)
In previous studies, a microbial fuel cell (MFC) was developed as a potential sensor that detects iron in water. However, to realize such an application in practice, the electrical signal generation of the MFC must be improved. Therefore, in this study, we investigated several measures to optimize the electrical signals of the MFC including (i) changing the anode spacing, (ii) testing different oxygen supply rates, (iii) testing different external resistances, and (iv) testing a new electrode material. An anode spacing of 2 cm was found to be optimal as the MFC generated a current that was at least 2-fold higher than any other anode spacing investigated. To limit oxygen diffusion from the cathode to the anode, an optimal cathode air flow rate of 1.8 ml min-1 was found, which corresponds to an oxygen supply rate of 0.286 mg min-1. By a polarization experiment, a 60-Ω external resistance ensured the most stable MFC-generated current , which is compulsory for the use of the device as a biosensor. Finally, activated carbon was shown to be an excellent material to improve electrical signal generation by 2-fold in comparison with graphite felt and graphite granules. These reported results will be the basis of further development of the MFC toward a practical biosensor.